2018
DOI: 10.1021/acs.biomac.8b00272
|View full text |Cite
|
Sign up to set email alerts
|

Co-Delivery of Doxorubicin and Anti-BCL-2 siRNA by pH-Responsive Polymeric Vector to Overcome Drug Resistance in In Vitro and In Vivo HepG2 Hepatoma Model

Abstract: Drug resistance, developed through multiple mechanisms, is a major hindrance to successful chemotherapy of tumor. Combination therapy of chemotherapeutic drugs and siRNA represents an emerging strategy which may improve anticancer effect by synergistic actions. In this study, triblock copolymer of poly(ethylene glycol)- block-poly(l-lysine)- block-poly aspartyl ( N-( N', N'-diisopropylaminoethyl)) (PEG-PLL-PAsp(DIP)) was synthesized for the first time to enable the codelivery of BCL-2 siRNA and DOX. The system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 42 publications
(76 reference statements)
0
58
0
Order By: Relevance
“…By contrast, the treatment of free DOX induced obvious intercellular vacuolation and dissolution of myocardial fibers, showing significant cardiotoxicity. This result suggested that the GH-DPP nanoparticles were biocompatible and useful for the delivery of chemotherapy drugs (Sun et al, 2018). Compared with nano-formulations for delivery DOX or siRNA alone, siRNA/DOX/GH-DPP nanoparticles showed stronger anti-tumor effect, indicating combination therapy could improve the anti-tumor efficiency by enhancing the sensitivity of cancer cells for chemotherapy drugs through inhibiting the expression of Bcl-2 protein (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…By contrast, the treatment of free DOX induced obvious intercellular vacuolation and dissolution of myocardial fibers, showing significant cardiotoxicity. This result suggested that the GH-DPP nanoparticles were biocompatible and useful for the delivery of chemotherapy drugs (Sun et al, 2018). Compared with nano-formulations for delivery DOX or siRNA alone, siRNA/DOX/GH-DPP nanoparticles showed stronger anti-tumor effect, indicating combination therapy could improve the anti-tumor efficiency by enhancing the sensitivity of cancer cells for chemotherapy drugs through inhibiting the expression of Bcl-2 protein (Chen et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, the drug release was slower at pH 7.4. The possible explanation is that the electrostatic interaction between positive segments (PEI) and negative segments (siRNA, GA-HA) is weak at lower pH value, leading to rapid release of the drug from the nano-carriers (Sun et al, 2018). Compared to siRNA/DOX/GH-DPP nanoparticles, the siRNA/DOX/DPP released more drugs at the same time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biodistribution analysis in HepG2/adriamycin (ADM) tumor-bearing mice showed that NP accumulation was observed at the tumor site 6 h after injection, and reached a maximum at 24 h, lasting for as long as 48 h. Furthermore, the treatment with DOX/siRNA-loaded PAD-PEG-PLL NPs was able to reduce tumor growth and increase the survival of tumor-bearing mice compared to controls. Lastly, ex-vivo analysis of the tumors showed reduced Bcl-2 and Ki67 expression after treatment, suggesting the induction of apoptosis and reduced cellular proliferation, which led to the control of tumor growth in the treated mice [72]. Another similar nanosystem was recently developed by Wang and colleagues incorporating a disulfide bridge between PEG and PLL (PEG-SS-PLL) to induce PEG release in the endosomes and facilitation of siRNA delivery to the cytoplasm of cancer cells.…”
Section: Pll-derived Nanosystemsmentioning
confidence: 99%